Digital video advertising strategies : grow your brand with online videos - Jayawardena, Nirma; Ross, Mitchell; Quach, Sara; Thaichon, Park; Behl, Abhishek (Emerald Publishing Limited, 2025)
In an age of rapid technological evolution, Digital Video Advertising Strategies: Grow Your Brand with Online Videos provides a comprehensive guide to navigating the complex world of digital marketing. From 3D video and augmented reality (AR), to virtual reality (VR), mixed reality (MR), artificial intelligence (AI), blockchain, and high-definition video, this edited volume systematically outlines key digital media strategies, providing definitions and guidance on their integration into traditional marketing campaigns, and how they can significantly elevate consumer engagement and persuasion. Key topics include the role of immersive technologies, gamification, and AI in digital video advertising. The book serves as a useful resource for professionals specializing in ad design, equipping them with strategies for leveraging 3D, VR, and AR video formats. Moreover, researchers focused on gamification will find valuable insights into how game elements can enhance viewer interaction with digital video content. Ultimately, this text aims to empower marketers and researchers alike with the knowledge needed to optimize digital video advertisements, fostering improved consumer experiences and engagement in an increasingly digital marketplace.